ҚАРАҚАЛПАҚ ХАЛЫҚ ДƏСТАНЫ «ШƏРИЯР» ҲƏМ ОНЫ ҮЙРЕНИЎДИҢ ГЕЙПАРА МƏСЕЛЕЛЕРИ - Кеңесбаева, Ш.К. (SCIENCE and SOCIETY, 2020)
The article is devoted to the study of the genesis, genre and form peculiarities, national character of the epos «Shariyar», that is an epic work of Karakalpak folklore. The subjective points of view on these issues have beeb discussed. In conclusion, the author of the article to value objectively the national heritage, taking into account the ideas of national independense on the example of the epos «Shariyar».